Understanding spirit possession in the Philippines: a social representations approach. Issue 7 (9th August 2019) - Ang, Angelica Vidallo; Montiel, Cristina Jayme
ABSTRACT: Where there are diverse professionals and curers dealing with possession, differences in representations exist. This study uses social representations theory as a frame to examine both the representational overlaps and differences in possession among various Filipino health professionals and the lay distinctly socialised in Western biomedical and psychological lenses and in local religious and traditional folk beliefs. Themes were extracted from 12 individual interviews. Results showed five representational themes, namely: possession as sinakluban, as a vulnerability, as a disease, as kulam, and as being chosen. Findings were discussed in relation to the interface among religion, indigenous beliefs, psychopathological frame, and the Western biomedical model.